2002
DOI: 10.1089/089277902753483745
|View full text |Cite
|
Sign up to set email alerts
|

Office-Based Transurethral Microwave Thermotherapy Using the TherMatrx TMx-2000

Abstract: This study demonstrates that the TherMatrx TMx-2000 TUMT effectively treats symptomatic BPH in the physician office with minimal morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…125,126,133,143,159,160,[170][171][172][173][174] Only peak urine flow rate is presented in this section. Results for the other urodynamic outcomes are presented in Appendix 8.2, Table 50 and Appendix 9.2, comparisons 02:04-02:09.…”
Section: Urodynamic Outcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…125,126,133,143,159,160,[170][171][172][173][174] Only peak urine flow rate is presented in this section. Results for the other urodynamic outcomes are presented in Appendix 8.2, Table 50 and Appendix 9.2, comparisons 02:04-02:09.…”
Section: Urodynamic Outcomesmentioning
confidence: 99%
“…Out of the eligible studies, complications were reported in ten. 125,126,133,143,159,160,[170][171][172][173] Ten categories of complications were identified. Results regarding blood transfusion, urinary retention, urinary tract infection, strictures and urinary incontinence are presented in this section ( Figure 7).…”
Section: Complicationsmentioning
confidence: 99%
See 3 more Smart Citations